2018
DOI: 10.3390/cryst8070286
|View full text |Cite
|
Sign up to set email alerts
|

Development and In Vitro Evaluation of a Zerumbone Loaded Nanosuspension Drug Delivery System

Abstract: Zerumbone extracted from the volatile oil of rhizomes available from the Zinigiber zerumbet has promising pharmacological activity. However, it has poor aqueous solubility and dissolution characteristics. To improve this, a nanosuspension formulation of zerumbone was developed. Nanosuspensions were formulated using high-pressure homogenization (HPH) with sodium dodecyl sulphate (SDS) and hydroxypropylmethylcellulose (HPMC) as stabilizers; the formulation was optimized and freeze dried. The optimized nanosuspen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…HPMC-based nanosuspensions showed steric stabilization by getting adsorbed into the surface of the dispersed nanoparticles providing a steric hindrance [21]. e obtained zeta potential was reasonably good for a stable nanosuspension, and this matched with some reported values for HPMC-stabilized nanoparticles [22][23][24]. For the optimized SDS-stabilized nanosuspension, the value of the zeta potential was −40.75 ± 2.76 mV (Figure 1(d)).…”
Section: Effect Of Homogenization Cycle and Pressure On The Narsupporting
confidence: 76%
“…HPMC-based nanosuspensions showed steric stabilization by getting adsorbed into the surface of the dispersed nanoparticles providing a steric hindrance [21]. e obtained zeta potential was reasonably good for a stable nanosuspension, and this matched with some reported values for HPMC-stabilized nanoparticles [22][23][24]. For the optimized SDS-stabilized nanosuspension, the value of the zeta potential was −40.75 ± 2.76 mV (Figure 1(d)).…”
Section: Effect Of Homogenization Cycle and Pressure On The Narsupporting
confidence: 76%
“…In previous studies, it has been shown that the incorporation of SLS yields smaller particle sizes compared to other stabilisers. For instance, SLS was used previously to prepare zerumbone nanosuspensions, which showed a particle size distribution significantly lower than those obtained using hydroxypropyl methylcellulose (HPMC) as stabiliser [23]. Additionally, Elham et al [24] prepared glipizide formulations using HPMC, Tween 80, poloxamer and SLS as stabilisers.…”
Section: Discussionmentioning
confidence: 99%
“…It is completely soluble in dimethyl sulfoxide (DMSO) and ethanol but has extremely poor solubility in water (~1–1.5 mg/L at 25 °C) [ 34 , 58 ]. Zerumbone is highly lipophilic and the poor water solubility contributes to poor absorption, low oral bioavailability, and limited targeting to tissues and organs of interest [ 28 , 35 , 36 , 37 , 47 , 48 ]. The chemical structure and other physicochemical characteristics of zerumbone are presented in Figure 1 and Table 1 , respectively.…”
Section: Source Chemistry Physicochemical Properties and Pharmamentioning
confidence: 99%
“…The authors report an increase in solubility, stability, and dissolution profile of zerumbone nanosuspension as compared to zerumbone alone. The results from this study provide evidence of the potential of nanosuspension technology to enhance the therapeutic potential of zerumbone in the future and warrant further in-vivo evaluation [ 48 ].…”
Section: Formulation Development and Drug Delivery Strategies Of Zmentioning
confidence: 99%
See 1 more Smart Citation